2021
DOI: 10.1155/2021/7467156
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol‐Induced AMPK Activation Alleviates Cisplatin‐Induced Nephrotoxicity through the Mitochondrial‐Dependent Pathway without Compromising Its Anticancer Properties

Abstract: Nephrotoxicity is a common complication of cisplatin chemotherapy and, thus, limits the clinical application of cisplatin. In this work, the effects of catalpol (CAT), a bioactive ingredient extracted from Rehmannia glutinosa, on cisplatin-induced nephrotoxicity and antitumor efficacy were comprehensively investigated. Specifically, the protective effect of CAT on cisplatin-induced injury was explored in mice and HK-2 cells. In vivo, CAT administration strikingly suppressed cisplatin-induced renal dysfunction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the current work, cisplatin caused downregulation of ovarian AMPK mRNA expression compared to the control group. Cisplatin has been reported to cause renal injury through the downregulation of AMPK expression [86,87]. In contrast, melatonin co-administration with cisplatin increased the expression of AMPK mRNA in the ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, cisplatin caused downregulation of ovarian AMPK mRNA expression compared to the control group. Cisplatin has been reported to cause renal injury through the downregulation of AMPK expression [86,87]. In contrast, melatonin co-administration with cisplatin increased the expression of AMPK mRNA in the ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that inhibition of autophagy accelerated ROS production and apoptosis induced by CP, while its activation reversed these effects ( Zhao et al, 2017 ). Moreover, activation of AMPK attenuated CP-induced AKI by improving mitochondrial function and suppressing the formation of ROS and apoptosis responses caused by CP, all of which effects were abolished upon AMPK inhibition ( Zhang J. et al, 2021 ). Furthermore, restoration of autophagy flux by polydatin ameliorated CP-induced oxidative stress, inflammation, and cell apoptosis, thereby alleviating CP-induced AKI ( Li et al, 2022c ).…”
Section: Autophagy In Cp-induced Akimentioning
confidence: 99%
“…In particular, the dysfunction of the mitochondrial respiratory chain results in the further excess production of ROS that contributes to severe kidney injury [20]. Consequently, the mitochondrial dysfunction induced by the treatment with cisplatin could be considered as due to increased levels of ROS resulting in various cellular apoptosis including kidney cells [2,21]. Increased levels of ROS can also contribute to the tubular cell apoptosis in kidney, thereby causing more severe kidney injury during AKI [22].…”
Section: Ros and Autophagy In Cisplatin-induced Acute Kidney Injurymentioning
confidence: 99%